2000
DOI: 10.1124/mol.57.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dopamine D2Receptor Signaling by Actin-Binding Protein (ABP-280)

Abstract: Proteins that bind to G protein-coupled receptors have recently been identified as regulators of receptor anchoring and signaling. In this study, actin-binding protein 280 (ABP-280), a widely expressed cytoskeleton-associated protein that plays an important role in regulating cell morphology and motility, was found to associate with the third cytoplasmic loop of dopamine D(2) receptors. The specificity of this interaction was originally identified in a yeast two-hybrid screen and confirmed by protein binding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 34 publications
5
100
1
Order By: Relevance
“…The actin binding protein filamin A (ABP-280), a cytoskeleton-associated protein involved in cell morphology and motility, interacts with the IL3 of D2 and D3 receptors [81]. These same regions also mediate the interaction of D2/D3 receptors with protein 4.1N, the neuronal form of the 4.1 family of cytoskeletal proteins implicated in linking the spectrin-actin cytoskeleton to the plasma membrane [80].…”
Section: D2 Drips In Dendritic Spinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin binding protein filamin A (ABP-280), a cytoskeleton-associated protein involved in cell morphology and motility, interacts with the IL3 of D2 and D3 receptors [81]. These same regions also mediate the interaction of D2/D3 receptors with protein 4.1N, the neuronal form of the 4.1 family of cytoskeletal proteins implicated in linking the spectrin-actin cytoskeleton to the plasma membrane [80].…”
Section: D2 Drips In Dendritic Spinesmentioning
confidence: 99%
“…Besides short peptide sequences involved in G protein and arrestin binding, the remaining portions of these intracellular domains are presumably free to interact with other proteins. Using approaches such as co-immunoprecipitation and the yeast two-hybrid system, an increasing number of DRIPs are being identified [41][42][43]53,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. The confirmed DRIPs and their suggested functions are summarized in Table 1.…”
mentioning
confidence: 99%
“…Proper attachment of dopamine D 2 receptors to the actin cytoskeleton through the actin-binding protein filamin A has been found to affect cell-surface clustering of this receptor (20). To analyze the plasma membrane expression pattern of A 2A R as a function of its ability to bind ␣-actinin, immunofluorescence experiments with A 2A R-FLAG-and A 2A ⌬CTR-FLAGtransfected HEK-293 cells were performed.…”
Section: Fig 3 Colocalization and Co-immunoprecipitation Of A 2a R mentioning
confidence: 99%
“…Recent studies have identified filamin A, another actin-cross-linking protein similar to ␣-actinin, as an intracellular binding partner for other heptaspanning membrane receptors, viz. the dopamine D 2 and D 3 receptors (20,21), the calcium-sensing receptor (22), and metabotropic glutamate receptors (23). A role for these interactions in the proper membrane targeting and synaptic localization of all these receptors has been proposed.…”
Section: Fig 3 Colocalization and Co-immunoprecipitation Of A 2a R mentioning
confidence: 99%
“…Filamin A is known to bind to various membrane and signaling molecules, see reviews (Stossel et al, 2001;van der Flier and Sonnenberg, 2001)}. More recently different laboratories, including our own, demonstrated that filamin A associates with various GPCRs, such as the D2 and D3 dopamine receptors (Li et al, 2000;Lin et al, 2001), the calcium-sensing receptor (CaR) (Awata et al, 2001;Hjalm et al, 2001), the metabotropic glutamate receptor type 7 (Enz, 2002), alpha1-adrenergic receptors (Zhang et al, 2004), calcitonin receptor (Seck et al, 2003) and the mu opioid receptor (MOP) (Onoprishvili et al, 2003). In some cases, such as the calcium sensing receptor and the MOP, the binding of filamin A is to the carboxyl tail, while for other receptors, such as the D2 and D3 dopamine receptors, the binding is to the third cytoplasmic loop.…”
Section: Introductionmentioning
confidence: 98%